Small-Size Meandered Loop Antenna for WLAN Dongle Devices. (13th February 2014) - Chen, Wen-Shan; Cheng, Chien-Min; Lee, Da-Huei; Ciou, Chun-Lin; Sin, Wei-Syun; Cai, Guang-Yuan
Abstract : This paper proposes a loop-type USB dongle antenna, which is fabricated on a 1.6 mm thick FR-4 substrate for WLAN band systems. The front side of substrate consists of a 50-ohm coaxial line and a multiarm monopole antenna, while the back side has a meandered loop antenna connected to the ground by two via holes. The meandered loop resonates half-wavelength mode at about 2.4 GHz and its higher modes. The higher modes excited by the multiarm monopole form the 5.2 GHz frequency band. The bandwidth of the antenna covers the IEEE802.11 a/b/g WLAN applications. The overall dimensions of the antenna of 30 × 13.75 × 1.6 mm 3 with an antenna area of 7.5 × 13.75 mm 2 and a planar structure are exactly suitable for applying in dongle devices. The measured results of radiation patterns, antenna gain, and radiation efficiency are also proposed and discussed in the paper.